FAKTOR PENDORONG ORANG TUA MENYEKOLAHKAN ANAKNYA DI MADRASAH DINIYAH AWALIYAH (MDA) AL MUHAJIRIN DI PERUMAHAN PURWODADI INDAH KELURAHAN SIDOMULYO BARAT KECAMATAN TAMPAN KOTA PEKANBARU - Ervalinda, Chindy Pratiwi; Baheram, Murni; ', Widiastuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Research it is based on parents causes their children to Madrasah Diniyah Awaliyah (MDA) the emigrants do not reside in environment mda the emigrants in a housing Purwodadi indah urban village west sidomulyo Kecamatan Tampan the city of Pekanbaru. Formulation problems will this research is a factor that is dominant of the internal factor to external driving parents educate their children in Madrasah Diniyah Awaliyah (MDA) the emigrants do not reside in environment mda the emigrants in a housing Purwodadi indah urban village west sidomulyo Kecamatan Tampan the city of Pekanbaru?. The purpose of this research is to find a factor that is driving parents educate their children in Madrasah Diniyah Awaliyah (MDA) the emigrants do not reside in environment mda the emigrants in a housing Purwodadi indah urban village west sidomulyo Kecamatan Tampan the city of Pekanbaru. Population in this study as many as 10 parents and research sample areas 51 parents with critical level 10, sample used is proporsionate stratified random sampling. An instrument data collection that is chief with 40 a statement and if the trial live 34 a statement valid for in made instrument research. Based on the results of the analysis that have been conducted by then a conclusion can be drawn to the result of this research be seen that in good, with the 61,74 % .Kata Kunci: factor, factors driving parents, educate their children in madrasah diniyah awaliyah (mda)